2017
DOI: 10.1038/srep42748
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the Apoptotic Resistance of Non-Small-Cell Lung Carcinoma towards TRAIL by Natural Product Toosendanin

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) selectively triggers cancer cell death via its association with death receptors on the cell membrane, but exerts negligible side effects on normal cells. However, some non-small-cell lung carcinoma (NSCLC) patients exhibited resistance to TRAIL treatment in clinical trials, and the mechanism varies. In this study, we described for the first time that toosendanin (TSN), a triterpenoid derivative used in Chinese medicine for pain management, could s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Thus, TAZ is important to keep the stabilization of mitochondrial outer membrane. 19,20 Previous studies have reported that TAZ is overexpressed in multiple cancers. 32,33 Furthermore, research has indicated that TAZ promotes drug resistance in some cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TAZ is important to keep the stabilization of mitochondrial outer membrane. 19,20 Previous studies have reported that TAZ is overexpressed in multiple cancers. 32,33 Furthermore, research has indicated that TAZ promotes drug resistance in some cancers.…”
Section: Discussionmentioning
confidence: 99%
“…TAZ which is targeted by miR-26b is a mitochondriarelated protein that negatively regulates apoptosis, 19,20 we next studied the role of miR-26b/TAZ axis in cisplatin-induced mitochondrial apoptosis pathway in PC9/ R and A549/R. Results of JC-1 staining showed that overexpression of miR-26b obviously increased the effect of cisplatin on breaking the MMP.…”
Section: Restoration Of Mir-26b Expression Targets Taz To Increase Thmentioning
confidence: 99%
“…More than two-thirds of lung cancer patients are diagnosed at an advance stage (III–IV), and intrinsic and/or acquired resistance to treatment represent major obstacles to the successful treatment of patients with advanced disease (1,2). As compared to other types of lung cancer, non-small cell lung carcinomas (NSCLC) is less prone to undergo spontaneous and treatment-induced apoptosis (3), suggesting that deficiencies in the apoptotic process may be responsible for their and/or acquired resistance to chemotherapy (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, they have been long documented to be toxic drugs [5,6]. Recently, an increasing number of studies have demonstrated the promising anti-tumor efficacy and insecticidal activity of TSN [7][8][9][10][11][12][13]. However, TSN was also reported to induce serious hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%